Pengaruh Promosi, Pelayanan, Lokasi Dan Tingkat Bunga Terhadap Minat Nasabah Bkm - Sumarmi, Saptaningsih (Akmenika, 2015)
The purpose of this research is to analyze the influence between variables promotions, service, location, interest rates on customers interest BKM Seyegan District of Sleman Yogyakarta. The respondents were citizens of an advanced society members BKM number of 130 people. The sampling technique used in this research is by using the Simple Random Sampling. Models were analyzed using software Partial Least Square (PLS). Based on results of analysis show that the variable of the promotion and the location proved to have a positive and significant effect on customer interest. While aspects of the service and interest rates are not shown to affect the interest of the customer.